2011
DOI: 10.1038/nature10147
|View full text |Cite
|
Sign up to set email alerts
|

Heart regeneration

Abstract: Preface Heart failure plagues industrialized nations, killing more people than any other disease. Heart failure usually results from a deficiency of cardiomyocytes, and a robust therapy to regenerate lost myocardium could help millions of patients a year. Heart regeneration is well documented in lower vertebrates and in developing mammals. After we are born, however, human heart regeneration becomes limited. In this article, Laflamme and Murry review the innate barriers to heart regeneration, the evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
982
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,155 publications
(998 citation statements)
references
References 93 publications
(119 reference statements)
7
982
0
9
Order By: Relevance
“…The pores of the nanofibrous patch permit the surrounding microvessels to grow into patch easily 17, which maintains better survival and growth of the transplanted MSCs. Optimization of the size of the pores in the patch will help to maximize vascularization within the implant and minimizes fibrosis around it 3. Moreover, the porous patch will allow pericardial fluid to stimulate the survival of the loaded MSCs, as the pericardial fluid from patients with ischaemic heart disease is enriched in growth factors such as VEGF and bFGF released from pericardial and epicardial cells as well as from the myocardium 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pores of the nanofibrous patch permit the surrounding microvessels to grow into patch easily 17, which maintains better survival and growth of the transplanted MSCs. Optimization of the size of the pores in the patch will help to maximize vascularization within the implant and minimizes fibrosis around it 3. Moreover, the porous patch will allow pericardial fluid to stimulate the survival of the loaded MSCs, as the pericardial fluid from patients with ischaemic heart disease is enriched in growth factors such as VEGF and bFGF released from pericardial and epicardial cells as well as from the myocardium 23.…”
Section: Discussionmentioning
confidence: 99%
“…Resent preclinical studies and clinical trails have shown that stems cell transplantation may be an effective way to improve cardiac function and attenuate adverse ventricular remodelling of the ischaemic myocardium 3, 4. There are several candidate stem cells for cardiac transplantation that have been recently evaluated 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with fish and amphibians, adult mammals have very limited capacity for myocardial regeneration (136), which is overwhelmed by the massive sudden loss of cardiomyocytes following infarction. Over the last 15 years, a wide range of cell therapy approaches has been tested in attempts to regenerate the injured human myocardium, with little success (137)(138)(139). Although beneficial actions have been reported with several different types of cell therapy, in many cases, protection of the infarcted myocardium was attributed to paracrine effects and to the modulation of inflammatory and fibrogenic signals rather than to activation of a regenerative program.…”
Section: The Cardiac Ecm In Metabolic Diseasementioning
confidence: 99%
“…[11][12][13] PSCs spontaneously differentiate into CMCs but, unfortunately, the efficiency of this process is extremely low (0.1-1%). Over the last few years, several methods have been proposed to improve the efficiency of this process; 14,15 however, inducing a cardiac fate is still extremely difficult, so easy and reliable approaches for the evaluation of differentiation strategies are needed.…”
Section: The Lvv Systemmentioning
confidence: 99%